Involvement of nervous system in cattle and buffaloes due to Pasteurella multocida B:2 infection: A review of clinicopathological and pathophysiological changes - Marza, Ali Dhiaa; Abdullah, Faez Firdaus Jesse; Ahmed, Ihsan Muneer; Chung, Eric Lim Teik; Ibrahim, Hayder Hamzah; Zamri-Saad, Mohd; Omar, Abdul Rahman; Abu Bakar, Md Zuki; Saharee, Abdul Aziz; Haron, Abdul Wahid; et al. (Journal of Advanced Veterinary and Animal Research, 2015)
Hemorrhagic septicemia (HS) is an acute septicemic disease principally affecting cattle and buffaloes caused by specific serotypes B:2 and E:2 of Pasteurella multocida in Asia and Africa, respectively. Despite continuing researches on pathogenesis of P. multocida for several decades, the mechanisms by which these bacteria develop the diseases are poorly understood. Although the involvement of the nervous system in the disease progress of HS is rare under natural conditions, few reports indicated the involvement of the nervous system in outbreaks of HS in cattle and buffaloes. Additionally, recent pathogenesis studies in both mouse and buffalo experimental models reported the involvement of nervous system due to P. multocida B:2, with bacteriological and histopathological evidences. In this review, we summarized and discussed the updates on the involvement of the nervous system in pathogenesis of HS focusing on clinical signs, pathological and pathophysiological changes. http://dx.doi.org/10.5455/javar.2015.b99